Can policy-makers think like designers? - Adler, Natalia (2014)
This is the poster used by Natalia Adler, from Unicef, at the Doing De velopment Differently workshop in 2014. Can policy-makers think like d esigners? Since 2012, UNICEF has been supporting two autonomous govern ments in Nicaragua to develop empathy-driven policies for children. Wh ile policies are the final product, the goal of the Designing for Chil dren Initiative is to make government officials think like designers. A good policy or service is nothing without active and engaged frontli ne workers. From the onset, our objective was to transform public empl oyees into ‘public entrepreneurs.’ In doing so, we have disrupted the traditional assumptions about participatory governance, where it norma lly suffices to hold a meeting and have people talk about their needs and aspirations. For participation to work, government officials have to relearn how to listen. They have to let go of pre-determined assump tions and their expert status, and put themselves in the shoes of the people they are trying to reach. This is the process of empathy-driven policy-making. For the past two years, we have used a Human Centered Design (HCD) approach to make this happen. While HCD is often seen as an innovation in itself, for us, it’s just a means to an end: common-s ense development.